BODIPY functionalized o-carborane dyads for low-energy photosensitization. Issue 6 (8th December 2014) - Jin, Guo Fan; Cho, Yang-Jin; Wee, Kyung-Ryang; Hong, Seong Ahn; Suh, Il-Hwan; Son, Ho-Jin; Lee, Jong-Dae; Han, Won-Sik; Cho, Dae Won; Kang, Sang Ook
Abstract : Bodipy- o -carborane dyads undergo a photo-induced electron transfer (PET) process under low energy visible light sensitization and their PET efficiencies are in the 63–71% range. Abstract : A new type of organic dyad that can induce low-energy photosensitization has been developed; electron donor and electron acceptor units are boron dipyrromethene (BODIPY) and ortho -carborane ( o -Cb), respectively. The new dyads consist of a V-shaped BODIPY-( o -Cb)-BODIPY molecular array in which two BODIPY units are substituted onto two adjacent carbon atoms of the central o -Cb. In the presence of the o -Cb unit, as an electron acceptor, significant fluorescence quenching was observed which indicated that photoinduced electron transfer (PET) had occurred from the end-on BODIPY units to the central o -Cb with PET efficiencies of 63–71%. As a result, the corresponding cationic and anionic species that are responsible for the charge transfer state were detected by the serial spectroelectrochemical studies: cationic BODIPY radicals at 400 nm at the applied voltage of 1.44 V and broad absorption bands of anionic o -Cb radicals in the range of 250–490 nm at −1.84 V. Transient absorption studies further confirmed the BODIPY radical anion at 540 nm and the o -Cb radical anion at 350–475 nm with a structureless broad band.